Lipid emulsions prevent postoperative abdominal adhesions - Sirovy, Miroslav; Krupova, Marketa; Hyspler, Radomir; Ticha, Alena; Kolackova, Martina; Andrys, Ctirad; Radochova, Vera; Astapenko, David; Odlozilová, Sarka; Kotek, Jiří; Zajak, Jan; Paral, Jiri (Asian journal of surgery, 2023)
INTRODUCTION: Adhesions are the most common cause of long-term morbidity after abdominal surgery and most often cause various forms of intestinal passage disorders ranging from partial obstruction to complete, life-threatening intestinal obstruction. The aim of the present study was to evaluate the protective effect of intraperitoneally administered lipid emulsions on the formation of adhesions in larger animal model, as the lubricating effect of phospholipids and the mechanical barrier of the lipid component are combined with the anti-inflammatory effect of fish oil. METHODS: Thirty-one female domestic pigs were randomly divided into three groups. At the end of the surgical procedure, a lipid emulsion or saline solution was applied intraperitoneally. After 14 days, an independent macroscopic, histological and immunohistochemical evaluation of the adhesions were performed. RESULTS: Intraperitoneal administration of lipid emulsions significantly reduced the incidence of intra-abdominal adhesions. Microscopic examination demonstrated a significant reduction in the number of inflammatory elements and the amount of collagen in the adhesions, especially after administration of the fish oil-based emulsion. A simultaneous decrease in neovascularization was observed in the adhesions. Evaluation of the intestinal anastomosis did not reveal significant differences in healing between the groups. CONCLUSION: Intraperitoneal administration of lipid emulsions can reduce the development of postoperative intra-abdominal adhesions by the combined action of phospholipids as important lubricants and lipids as a mechanical barrier. Their effect is caused by a reduction in proinflammatory and profibrotic mediators. At the same time, intraperitoneal administration of lipid emulsions does not impair healing of the anastomosis in larger animal model.
Keywords: Animals; Fish Oils; Emulsions; adheze tkání; Female; emulze; zvířata; anastomóza chirurgická; Postoperative Complications; rybí oleje; Anastomosis, Surgical; pooperační komplikace; Tissue Adhesions; ženské pohlaví